Marketing Strategy of Agriku Product (Tuna Chili Sauce) at Muhammadiyah University of Parepare - Setiawan, Heri; Nurhapsa; Abd. Rahim (FAKULTAS PERTANIAN UNIVERSITAS RATU SAMBAN, 2025)
Tuna chili sauce is one of the local processed products from Agriku MSME, which is marketed within the Muhammadiyah University of Parepare. This product has a distinctive taste and considerable market potential among students and academic staff. However, the marketing of this product still faces several challenges, such as limited production capacity and suboptimal promotional efforts. The objectives of this study are: 1) To identify internal and external factors affecting the sales of Agriku's tuna chili sauce at Muhammadiyah University of Parepare; and 2) To analyze effective marketing strategies to increase its sales within the campus environment. This research employs a descriptive quantitative method, utilizing a SWOT analysis approach, and data collection techniques that include observation, questionnaires, and documentation. The results show that the product's strengths lie in its flavor quality and attractive packaging, while its weaknesses are limited promotion and production capacity. Opportunities include high market demand and support from the university, whereas threats come from competing products. This study yielded several practical marketing strategies, including optimizing product strengths through targeted social media promotion, expanding distribution reach beyond the campus, incrementally increasing production capacity, and developing product variations to address market competition. These strategies were derived from a SWOT analysis that positioned the product in Quadrant II (diversification strategy), where the organization possesses internal strengths but faces external threats.